2005
DOI: 10.1186/1471-2407-5-131
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II – study evaluating EGFR targeting therapy with Cetuximab in combination with radiotherapy and chemotherapy for patients with locally advanced pancreatic cancer – PARC: study protocol [ISRCTN56652283]

Abstract: Background: Pancreatic cancer is the fourth commonest cause of death from cancer in men and women. Advantages in surgical techniques, radiation therapy techniques, chemotherapeutic regimes, and different combined-modality approaches have yielded only a modest impact on the prognosis of patients with pancreatic cancer. Thus there is clearly a need for additional strategies. One approach involves using the identification of a number of molecular targets that may be responsible for the resistance of cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 37 publications
0
34
0
3
Order By: Relevance
“…a : Normierung auf das Volumen zu Beginn der Substanzbehandlung; b : Normierung auf das Volumen zum Zeitpunkt der Bestrahlung. ments on the anti-EGFR monoclonal antibody C225, which does not radiosensitize FaDu tumor cells in vitro either, local tumor control after combination with fractionated irradiation in vivo was improved by inhibition of clonogenic cell repopulation and improvement of reoxygenation [21,23]. Both mechanisms can be investigated only in vivo using long-term fractionated irradiation schedules and local control as experimental endpoint [5,22].…”
Section: Discussionmentioning
confidence: 99%
“…a : Normierung auf das Volumen zu Beginn der Substanzbehandlung; b : Normierung auf das Volumen zum Zeitpunkt der Bestrahlung. ments on the anti-EGFR monoclonal antibody C225, which does not radiosensitize FaDu tumor cells in vitro either, local tumor control after combination with fractionated irradiation in vivo was improved by inhibition of clonogenic cell repopulation and improvement of reoxygenation [21,23]. Both mechanisms can be investigated only in vivo using long-term fractionated irradiation schedules and local control as experimental endpoint [5,22].…”
Section: Discussionmentioning
confidence: 99%
“…61 Further clinical investigations are ongoing. 62 In the group of tyrosine kinase inhibitors, gefitinib (Iressa ' ) inhibits pancreatic cancer cell growth and invasiveness by blocking ErbB1-dependent pathways, suggesting that gefitinib may offer a new approach for the treatment of pancreatic cancer. 63 A phase-I trial reported, however, that the combination of gefitinib, capecitabine and radiation in pancreatic cancer patients resulted in significant patient toxicity.…”
mentioning
confidence: 99%
“…The most frequent grade 3 or 4 toxicities were neutropenia, asthenia, abdominal pain and thrombocytopenia [12,16] . A phase II trial evaluating cetuximab therapy in combination with modulated radiation therapy (IMRT) and gemcitabine is currently recruiting patients [17] .…”
Section: Pancreatic Cancer -Outlook: Targeted Therapymentioning
confidence: 99%